Interpretive Structural Modelling for Challenging Issues in JIT Supply Chain: Product Variety Perceptive - Vijay Bhaskar Mahajan; J. R. Jadhav; Dr. V. R. Kalamkar; Dr. B. E. Narkhede (International Journal of Supply Chain Management, 2013)
The success of JIT in Japan inspired many organizations to adopt JIT to the supply chain in order to reduce the waste and cost. These organizations have to face inherent challenging issues and complexities while implementing JIT concepts in supply chain. The manufacturer must be in position to identify challenging issues, its consequences so as to design a robust and reliable supply chain accordingly otherwise the manufacturing system may not provide the desired results. The focus of this paper is on the significant challenging issues in JIT supply chain from product variety perspective. Some challenging issues act as driver for sustainable implementation of JIT supply chain. For adoption of JIT supply chain, significant issues must be identified, analysed and discussed. In this research, study factors are the challenging issues for sustainable JIT supply chain implementation. Authors have identified ten significant issues from literature review. The main objectives are to identify and rank the challenging issues for implementation, to develop and to analysed the interaction between identified challenging issues using ISM and to prepare a framework for successful JIT supply chain implementation.